Tagabawa bagobo folk narratives structures - JOHN REY A. ALERIA (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this research is to examine the folk tales of the Tagabawa Bagobo, an indigenous group living in the southern Philippines, and to make comparisons and contrasts between their narrative structures. Narratives are aesthetically pleasing because of the careful planning and execution of their syntactic construction. Despite this, there need to be more studies that dissect the narrative architecture of folk tales.Method: This study employs a qualitative approach to inquiry, specifically a descriptive research layout. Tzvetan Todorov, a French-Bulgarian literary theorist, provided the theoretical foundation for this approach, which he called "narratology." In this analysis, ten Tagabawa Bagobo folktales are used.Findings: The study found that all ten folk tales used contained narrative units. You can think of these narrative units as the building blocks of any story or narrative. These basic elements consist of nouns, verbs, and adjectives. Predicates are acted upon by these, and they can take the form of either immutable states or mutable qualities and conditions. Propositions form the basis of folk tales. The two parts of a proposition are (a) the thing being discussed or named (the argument or entity) and (b) an assertion or predicate about the argument. A proposition is a sentence with a subject and a predicate. Todorov’s five-stage model of narrative, which begins with equilibrium and concludes with restoration, is reflected in the propositions. These phases are typical of narratives, beginning with the exposition and ending with the conclusion.Implications/Novel Contribution: The current author argues that Todorov’s structural theory provides a useful lens through which to examine the contemporary relevance of folk tales